2022
DOI: 10.1021/jacs.1c10447
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Photoelectrochemical Coupling Reactions of para-Aminobenzoic Acid on Nanostructured Gold Electrodes

Abstract: Surface plasmon resonance (SPR) bridges photonics and photoelectrochemistry by providing an effective interaction between absorption and confinement of light to surface electrons of plasmonic metal nanostructures (PMNs). SPR enhances the Raman intensity enormously in surface-enhanced Raman spectroscopy (SERS) and leads to the plasmon-mediated chemical reaction on the surface of nanostructured metal electrodes. To observe variations in chemical reactivity and selectivity, we studied the SPR photoelectrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…22−25 In contrast, the plasmon effects on regulating electrocatalytic pathways as well as the underlying mechanism have been least investigated. 26,27 In this work, the Au@Pt nanoparticles with the plasmonic core and active shell are designed initially to boost concurrently the EOR activity and C1 selectivity in alkaline media under the visible light illumination at room temperature, during which local heating and energetic carriers make a mixed contribution with the local heating effect being dominant. In situ attenuated total reflection−surface enhanced infrared absorption spectroscopy (ATR-SEIRAS), 28−32 as a nondestructive surface sensitive analytical tool, is used to track the real-time evolution of surface species at different applied potentials with or without illumination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22−25 In contrast, the plasmon effects on regulating electrocatalytic pathways as well as the underlying mechanism have been least investigated. 26,27 In this work, the Au@Pt nanoparticles with the plasmonic core and active shell are designed initially to boost concurrently the EOR activity and C1 selectivity in alkaline media under the visible light illumination at room temperature, during which local heating and energetic carriers make a mixed contribution with the local heating effect being dominant. In situ attenuated total reflection−surface enhanced infrared absorption spectroscopy (ATR-SEIRAS), 28−32 as a nondestructive surface sensitive analytical tool, is used to track the real-time evolution of surface species at different applied potentials with or without illumination.…”
mentioning
confidence: 99%
“…Notably, if the LSPR occurs in the visible region, solar energy can be effectively utilized. So far, the relevant reports were mostly focused on the synthesis of various plasmonic nanostructures with a primary target to increase the catalytic activity. In contrast, the plasmon effects on regulating electrocatalytic pathways as well as the underlying mechanism have been least investigated. , …”
mentioning
confidence: 99%
“…29 Recently, Wu et al reported the difference between electro-oxidation and LSPR-assisted electro-oxidation in surface-enhanced Raman spectroscopic (SERS) measurements. 30 Here in this work, electrode potentials are introduced as a visualization tool to adjust surface potentials (Scheme 1a) for quantifying the energy of hot electrons. Several hot electron-sensitive chemicals including 4-nitrothiophenol (4-NTP) and 4-iodothiophenol (4-ITP) were coated on 60 nm Au NPs as SERS probes that can reflect the hot electron energy.…”
mentioning
confidence: 99%
“…Gargiulo and co-workers quantified the energy of hot holes using EC–dark field scatter measurements . Recently, Wu et al reported the difference between electro-oxidation and LSPR-assisted electro-oxidation in surface-enhanced Raman spectroscopic (SERS) measurements . Here in this work, electrode potentials are introduced as a visualization tool to adjust surface potentials (Scheme a) for quantifying the energy of hot electrons.…”
mentioning
confidence: 99%
“…Supported small GNPs are chemically reactive and have been used as effective heterogeneous catalysts in several chemical reactions under mild conditions . By shining visible light on the GNPs, the light energy can be harvested on the GNP surface through the localized surface plasmon resonance, which further decays through the non-radiative pathways into heat and high-energy hot electrons and holes to catalyze chemical reactions on the GNP surface. , The concentrated light field in the junctions can also greatly amplify signals of surface enhanced Raman spectroscopy (SERS), which has been used to monitor the organic reactions in situ and in real time up to the single-molecule level . To study the mechanism of chemical reactions, it is important to probe the intermediates.…”
Section: Introductionmentioning
confidence: 99%